2005
DOI: 10.1021/jm0505009
|View full text |Cite
|
Sign up to set email alerts
|

Alkyl-Substituted Polyaminohydroxamic Acids:  A Novel Class of Targeted Histone Deacetylase Inhibitors

Abstract: The reversible acetylation of histones is critical for regulation of eukaryotic gene expression. The histone deacetylase inhibitors trichostatin (TSA, 1), MS-275 (2) and suberoylanilide hydroxamic acid (SAHA, 3) arrest growth in transformed cells and in human tumor xenografts. However, 1-3 suffer from lack of specificity among the various HDAC isoforms, prompting us to design and synthesize polyaminohydroxamic acid (PAHA) derivatives 6-21. We felt that PAHAs would be selectively directed to chromatin and assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 26 publications
2
51
0
Order By: Relevance
“…We also found a previously unreported C-terminal acetylation at Lys 116 ( Figure 5; see Tables E4 and Table E5 and Figure E8). We confirmed the effect of acetylation on proteasome degradation, using histones that were purified from A549 cells treated with a combination of HDAC inhibitors (trichostatin, MS-275, and suberoylanilide hydroxamic acid) to produce hyperacetylated histones (26). In Figure 8, the Western blots show that hyperacetylated H3.3, which is purified from the treated cells, is less sensitive to degradation by 20S proteasomes than H3.3 from the control cells.…”
Section: Mechanism Of H33 Increase In Copd Involves Impaired Degradamentioning
confidence: 56%
“…We also found a previously unreported C-terminal acetylation at Lys 116 ( Figure 5; see Tables E4 and Table E5 and Figure E8). We confirmed the effect of acetylation on proteasome degradation, using histones that were purified from A549 cells treated with a combination of HDAC inhibitors (trichostatin, MS-275, and suberoylanilide hydroxamic acid) to produce hyperacetylated histones (26). In Figure 8, the Western blots show that hyperacetylated H3.3, which is purified from the treated cells, is less sensitive to degradation by 20S proteasomes than H3.3 from the control cells.…”
Section: Mechanism Of H33 Increase In Copd Involves Impaired Degradamentioning
confidence: 56%
“…8 The synthetic routes to PABA analogues 21-23 are shown in Schemes 1 and 2. Our initial strategy involved N-Boc protection 14 of 4-(amino)methylbenzoic acid 24, followed by coupling with o-nitroaniline (EDCI, HOBT, TEA) to form 25.…”
Section: Chemistrymentioning
confidence: 99%
“…8 The results of these studies are summarized in Table 1. PAHAs 6, 8, 9, 13, 17, 18, and 20 all produced greater than 50% inhibition, with compound 18 producing the greatest inhibition (88.7%).…”
Section: Biological Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Attaching them to proteins provides an elegant way to manipulate charge concentrations locally and alter DNA binding affinity (highly negatively charged due to phosphate backbone) to assume a compact (silenced) conformation. Recent papers showed that polyamines or polyamines analogs inhibit Lysine Specific Demethylase 1 (LSD1), a FADdependent histone demethylases, able to demethylate mono and dimethyl lysine 4 of histone H3, active marks of transcription (Huang et al, 2007;Shi et al, 2004) and they can block HDACs activity sitting in their catalytic pocket (Varghese et al, 2005). In a number of in vitro studies, polyamines can be crosslinked to glutamine tails of histones by transglutaminase 2 (TGase 2).…”
Section: Beyond Acetylation: Methylation Ubiquitylation Polyaminationmentioning
confidence: 99%